In search of value drivers in mergers and acquisitions: The Nordic evidence - Caspar Rose; Daniel Sørheim; Magnus Lerkerød (International Journal of Business Science & Applied Management (IJBSAM), 2017)
The international literature on M&As is extensive, but surprisingly little evidence exists for the Nordic countries. This article attempts to fill the gap by studying 184 merger announcements from 1995 to 2014. Our findings differ in a number of ways. First, we extend the current literature since we find that diversifying acquisitions generate a higher bidder abnormal return compared with focused transactions. A possible explanation is that in diversifying acquisitions acquirers overpay for target firms within their core industry because they overestimate operational synergies. The managerial implication is that the notion of core business should not restrict diversified value-enhancing M&As. Secondly, we find evidence that bidder abnormal returns depend not on the method of payment. The implication is that bidders may have more flexibility with regard to the financing of deals in the Nordic countries, because the acquirer's managers do not have to take into account any negative market reactions with regard to the payment method. Thirdly, we explore the relationship between cash flows and abnormal returns. Our results confirm current literature since we find that low-valued bidders with excessive free cash flows experience negative returns prior to an announcement. Furthermore, our results imply that a bidder company must be able convincingly to justify an acquisition to the market by communicating the presence of a sound and coherent integration plan.
Keywords: 650; M&A value creation; means of payment; free cash flow; diversifying acquisitions